152k views
2 votes
3(y − 11) = 18
i really need the help

User Alpakyol
by
4.9k points

1 Answer

3 votes

Answer:

y = 17

Explanation:

Isolate the variable y. Do the opposite of PEMDAS.

Note that:

PEMDAS is the order of operation and equals:

Parenthesis

Exponents (& Roots)

Multiplication

Division

Addition

Subtraction.

First, distribute 3 to all terms within the parenthesis:

3(y - 11) ⇒ (3 * y) + (3 * -11) ⇒ (3y) + (-33) ⇒ 3y - 33

Next, Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

First, add 33 to both sides of the equation:

3y - 33 (+33) = 18 (+33)

3y = 18 + 33

3y = 51

Next, divide 3 from both sides of the equation to isolate the variable, y:

(3y)/3 = (51)/3

y = 51/3

y = 17

y = 17 is your answer.

~

User Nafaa Boutefer
by
4.3k points